Role and regulation of chemotaxis and motility in the Rhizobium-legume symbiosis - Aroney, S (2021)
Fertilisers are used to provide crop plants with essential nutrients such as nitrogen but with a high energy cost and detrimental environmental effects. The symbiosis of legumes with rhizobia exhibits none of these problems since the bacteria provide fixed nitrogen directly to the plant. Further understanding of the initiation of symbiosis may enable improvements to the farming of crop legumes and enable the same processes to be mimicked in engineered systems of other crops. Although motility and chemotaxis are known to be crucial for competitive plant root colonisation (the first stage of symbiosis), little is known about their importance after this stage. In this thesis, I aimed to describe the importance of chemotaxis and motility in sequential stages of symbiosis up to the generation of root nodules filled with nitrogen-fixing rhizobia. To this end, the chemotaxis and motility systems of the model rhizobia Rhizobium leguminosarum biovar viciae 3841 (Rlv3841) were characterised, in both free-living and plant-associated states.